Antimicrobial Potential of Bacteria Associated with Marine Sea Slugs from North Sulawesi, Indonesia - Böhringer, Nils; Fisch, Katja M.; Schillo, Dorothee; Bara, Robert; Hertzer, Cora; Grein, Fabian; Eisenbarth, Jan-Hendrik; Kaligis, Fontje; Schneider, Tanja; Wägele, Heike; König, Gabriele M.; Schäberle, Till F. (Frontiers in Microbiology, 2017)
Nudibranchia, marine soft-bodied organisms, developed, due to the absence of a protective shell, different strategies to protect themselves against putative predators and fouling organisms. One strategy is to use chemical weapons to distract predators, as well as pathogenic microorganisms. Hence, these gastropods take advantage of the incorporation of chemical molecules. Thereby the original source of these natural products varies; it might be the food source, de novo synthesis from the sea slug, or biosynthesis by associated bacteria. These bioactive molecules applied by the slugs can become important drug leads for future medicinal drugs. To test the potential of the associated bacteria, the latter were isolated from their hosts, brought into culture and extracts were prepared and tested for antimicrobial activities. From 49 isolated bacterial strains 35 showed antibiotic activity. The most promising extracts were chosen for further testing against relevant pathogens. In that way three strains showing activity against methicillin resistant Staphylococcus aureus (MRSA) and one strain with activity against enterohemorrhagic Escherichia coli (EHEC), respectively, were identified. The obtained results indicate that the sea slug associated microbiome is a promising source for bacterial strains, which hold the potential for the biotechnological production of antibiotics.